Gender issues in safety and health at work: a review (Bilbao, 2003)
"Achieving gender equality in all aspects of employment is now a key European priority. It is a matter of rights, but it is also a matter of sound economic policy - especially considering the human and economic costs of injuries and ill health caused ."